2019
DOI: 10.3390/ijms20061352
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Genetic Diversity and Population Structure of Tunisian Durum Wheat Landraces Based on DArTseq Technology

Abstract: Tunisia, being part of the secondary center of diversity for durum wheat, has rich unexploited landraces that are being continuously lost and replaced by high yielding modern cultivars. This study aimed to investigate the genetic diversity and population structure of 196 durum wheat lines issued from landraces collected from Tunisia using Diversity Array Technology sequencing (DArTseq) and to understand possible ways of introduction in comparing them to landraces from surrounding countries. A total of 16,148 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
66
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(83 citation statements)
references
References 61 publications
12
66
2
Order By: Relevance
“…Italian landraces were characterized by a moderate level of genetic diversity (He = 0.26), which is comparable with that of Mediterranean (He = 0.24) or Tunisian and Iranian (He = 0.25) landraces, as revealed by the analysis of patterns of genetic diversity using AFLP (Moragues et al, 2007;Nazco et al, 2012) and DArT markers (Fayaz et al, 2018;Robbana et al, 2019), respectively. Relatively small differences in Nei and Shannon indices were observed moving from LR to MC, while we observed that a weak genetic bottleneck (i.e., loss of rare alleles) has been imposed by breeding programs on the old Italian durum wheat ( H = −0.09), suggesting that the overall molecular diversity of durum wheat has undergone moderate fluctuations during the 20th century (Maccaferri et al, 2005;Martos et al, 2005;Laidò et al, 2013).…”
Section: Genetic Diversity and Private Alleles Across Populationsmentioning
confidence: 95%
“…Italian landraces were characterized by a moderate level of genetic diversity (He = 0.26), which is comparable with that of Mediterranean (He = 0.24) or Tunisian and Iranian (He = 0.25) landraces, as revealed by the analysis of patterns of genetic diversity using AFLP (Moragues et al, 2007;Nazco et al, 2012) and DArT markers (Fayaz et al, 2018;Robbana et al, 2019), respectively. Relatively small differences in Nei and Shannon indices were observed moving from LR to MC, while we observed that a weak genetic bottleneck (i.e., loss of rare alleles) has been imposed by breeding programs on the old Italian durum wheat ( H = −0.09), suggesting that the overall molecular diversity of durum wheat has undergone moderate fluctuations during the 20th century (Maccaferri et al, 2005;Martos et al, 2005;Laidò et al, 2013).…”
Section: Genetic Diversity and Private Alleles Across Populationsmentioning
confidence: 95%
“…The assessment of genome-wide diversity by GBS provides robust estimates of diversity and has been increasingly adopted as a fast, high-throughput cost-effective tool for whole-genome genetic diversity analysis in large germplasm sets (16). The DArTseq (Diversity Array Technology sequence) markers, based on GBS (17), efficiently target low-copy-number sequences via a complexity reduction method and have been successfully applied for genetic diversity studies in different species (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…However, lower genetic diversity was observed in 33 Anatolian, 136 south Italian and 40 North-West African durum wheat landraces using 14, 44 and 29 SSR markers, respectively [2,12,23]. Low genetic diversity (PIC=0.1; He=0.25) was also observed in 196 Tunisian durum wheat accessions by Robbana et al [18], due i) to the use of biallelic DArTseq markers with lower informativeness level than multi-allelic SSR markers and ii) to a germplasm collection limited to 5 landraces. This variability between results suggests that capturing the maximum genetic diversity would depend essentially on the type of deployed markers, the number of landraces, the origin and geographical distribution (genetic backgrounds) of the studied collection.…”
Section: Genetic and Morphological Diversity Kept In Tunisian Durum Wmentioning
confidence: 91%
“…In our study, grain size didn't signi cantly differ between C1 and C2 suggesting that both clusters have indeed western Mediteranean origin. Moreover, Robbana et al [18] mentioned that most of Tunisian landraces were introduced from the early Carthage trade maritime activity in the Mediterranean Sea, through pathways from Lebanon, Greece and Italy.…”
Section: Population Structure Network Analysis and Relationships Betmentioning
confidence: 99%
See 1 more Smart Citation